2011
DOI: 10.1097/scs.0b013e31822e624f
|View full text |Cite
|
Sign up to set email alerts
|

Speech Outcomes and Velopharyngeal Function After Surgical Treatment of Velopharyngeal Insufficiency in Individuals With Signs of Velocardiofacial Syndrome

Abstract: Patients with VCFS presented similar speech function and VPF characteristics as patients with nonsyndromic SMCP. The surgery for velopharyngeal insufficiency correction was equally effective for the improvement and resolution of speech symptoms and VPF in patients with VCFS compared with the SMCP group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…However, in this case, the analysis made by listeners was based on the presence or the absence of hypernasality and not on the grading of the symptom. From the studies that classified hypernasality using a four-point scale, most found agreement that are similar to those reported in this study, ranging from fair to moderate (21) , moderate to good (27) , and moderate (28) . With regard to the use of training and this study, other researchers also reported improvement in intra-and interrater reliability after listener training (15) .…”
Section: Discussionsupporting
confidence: 70%
“…However, in this case, the analysis made by listeners was based on the presence or the absence of hypernasality and not on the grading of the symptom. From the studies that classified hypernasality using a four-point scale, most found agreement that are similar to those reported in this study, ranging from fair to moderate (21) , moderate to good (27) , and moderate (28) . With regard to the use of training and this study, other researchers also reported improvement in intra-and interrater reliability after listener training (15) .…”
Section: Discussionsupporting
confidence: 70%
“…In a handful of studies the inter- or intrarater reliability for the speech test were reported, indicating the validity of the test [21], [45], [50], [52], [53]. Others used the previously validated Cleft Audit Protocol for Speech [24] or Pittsburgh Weighted Speech Score [44], [48], [54].…”
Section: Resultsmentioning
confidence: 99%
“…Lower primary success rates for all patients with hypodynamic velopharynges, including those with 22qDS, supports the logic of segregating this group (which constitutes up to 25% of the population with VPD) from the larger cleft palate population [67]. In general, the speech outcome after surgery has been reported to be worse in patients with 22qDS than in patients without the syndrome [25], [36], [47], [49], [56], [79], [80], [81], but some patients with 22qDS fare as well as their non-syndromic counterparts [33], [39], [40], [46], [52], [61], [82].…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, these difficulties likely result from craniofacial dysmorphology including cleft palate and other anomalies that often require surgical intervention. Unfortunately, current surgical treatments are only effective in approximately 25% of patients [14, 15], suggesting mechanisms beyond oropharyngeal mechanics may contribute to pathology. Indeed, many cases of pediatric dysphagia in 22q11DS patients are not accompanied by overt craniofacial dysmorphology that requires surgical intervention [13, 16].…”
Section: Introductionmentioning
confidence: 99%